On Growing Operating Costs in the Armed Forces. Issue 4 (7th June 2019) - Hove, Kjetil Hatlebakk; Lillekvelland, Tobias
Abstract: Operating costs per unit of input or output are often claimed to grow faster in defence than elsewhere in the economy. In this paper, we outline several possible reasons as to why operating costs increase at higher rates in defence, including differences in the input factor mix and productivity growth, the technological complexity required to maintain the relative effect of weapon systems and a gradual reduction in the number of units and activity. We investigate whether operating costs grow at a faster rate than elsewhere in the economy, by estimating growth in real output unit costs in the Norwegian Armed Forces for the period 1994–2013, using activity as a measure of output. We find no increase beyond general inflation in structural (fixed) costs, whereas activity-based (variable) costs per unit of activity increase significantly.